PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL BERKAITAN DENGAN BERLAKUNYA UU NO. 2 TAHUN 2004 - Suhandi Suhandi (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
Harmonic, dynamic and fair industrial relations needs to be formed optimally based on values of five principals of Pancasila. Nowadays, the number of disagreements on industrial field are increasing and relatively more complex, Therefore, it requires quick, appropriate solution and reflecting fairness for parties involved both employees and manufacturers.